(untitled) (XXI Century. Spanish Literature and Culture, 2017)
The publication of Julio Llamazares’s La lluvia amarilla (1988) took place against the current, at a time when the Spanish narrative explored alternative and urban stylistic and thematic channels, far from the deep rural bond that this work demonstrates, nostalgia and funereal chant to abandonment irremissible of the small villages that populated, that still populate, the Spanish countryside. However, and despite this somewhat disconsolate nature with respect to the predominant narrative tendencies in the 80s of the 20th century, this work marked a milestone, became a standard, in a poetic voice of a reality that is not hidden or less socially considered was, is, less real.